PERANCANGAN APLIKASI ABSENSI PESERTA BIMBINGAN BELAJAR BERBASIS WEB DENGAN MENGGUNAKAN FRAMEWORK YII - Sri Rahayu; Muhamad Yusup; Sinta Puspita Dewi (Universitas Raharja, 2015)
Activities attendance of participants in a learning institution is generally done every meeting in order to determine whether students are sick , license , negligent , or late for any class. Then, the data will be entered into the data absentee participant, the participant data include NIP, Name, Class.. Attendance data on the participants learning institution can be used as an assessment to the level of discipline on each participant. It also serves to obtain attendance data summary for each participant at the end of the meeting. Attendance data of pre-existing participants can not meet the needs of the user at the time of charging participants for attendance officers are still using manual attendance register. Attendance manually participants will encounter some problems such as easily wear away, difficulty in data retrieval and slow time in the data processing is considered a need for change in a computerized system so that the information obtained are more accurate. It is because the system uses a database, where the data is stored in an integrated way. Construction of the system by using web yii framework has advantages which are small data size, the Security Concern framework to anticipate and put up a shield against the various security issues that may arise.